A Learning Design Methodology for Developing Short Learning Programmes in Further and Continuing Education. Issue 1 (23rd May 2018) - Buus, Lillian; Georgsen, Marianne
Over the past 5 years, teaching staff at the School of Continuing Education, VIA University College, Denmark, has been designing digitally supported teaching within diploma programmes and tailor-made courses in the fields of health, education, social sciences and management. More and more of these programmes and courses are designed as blended learning and are characterised by a short time cycle of design, delivery and completion. Despite a recent addition of learning design expertise to the organisation, there is a predominant tendency in design processes to focus on the technical setup, the content and the participants, and very little on the role of the teachers. The teachers' role is challenged by a number of issues in relation to the growing use of blended and online learning, e.g. the task of facilitating the learning processes of the participants in new ways; a higher degree of exposure as the teacher often becomes the sole point of contact in online environments; communication skills needed to facilitate dialogue and collaboration in an online environment; etc. Furthermore, involvement of teaching staff in co-creation of new learning designs require skills which many lecturers do not have when they enter the design team for the first time, among others skills to articulate their pedagogical principles and technological imagination. Over time, we in our roles as learning designers in the School of Continuing Education have developed, tested and refined a technique for user involvement in the design work, and teachers now work with our professional learning designer and course producer on redesigning courses or creating new module or courses. In these collaborative design processes, we have identified a number of challenges, which will be dealt with in our paper.